2019
DOI: 10.1177/0300060518819378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of OrthoPilot navigation system versus conventional manual total hip arthroplasty: A systematic review and meta‐analysis

Abstract: Objective This study was performed to compare the clinical efficacy between the OrthoPilot navigation system and conventional manual surgery in patients undergoing total hip arthroplasty. Methods The Embase, PubMed, CINAHL, and Cochrane databases were searched for clinical trials. The outcome measurements were the anteversion angle, inclination angle, and complications. Review Manager 5.3 statistical software was used for the data analysis. Results Significant differences were found in the femoral offset and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Approximately 25.7–85% of cases are placed in the safe zone. 12 , 20 22 There are also reports that the cup placement accuracy differs depending on patients’ BMI and surgeons’ experience. Callanan et al reported that while cup placement in the safe zone among experienced surgeons was 51.1%, the rate was 34.1% for inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25.7–85% of cases are placed in the safe zone. 12 , 20 22 There are also reports that the cup placement accuracy differs depending on patients’ BMI and surgeons’ experience. Callanan et al reported that while cup placement in the safe zone among experienced surgeons was 51.1%, the rate was 34.1% for inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, more than 1 million people worldwide have hip arthritis with refractory or permanent pain and dysfunction, and this number is expected to double in the next 20 years 5 . A number of clinical studies have shown that, compared with traditional THA, the use of surgery navigation systems can improve the accuracy of prosthesis placement, 139,140 hence reducing the incidence of postoperative displacement‐related complications.…”
Section: Computer‐assisted Orthopaedic Surgery Navigation Systemsmentioning
confidence: 99%
“…By detecting markers and displaying them in a virtual scene, the surgery instruments can be tracked in real time, and the information is transmitted to the orthopaedic surgeon in real time. A number of clinical studies have shown that compared with traditional THA, imageless navigation can improve the accuracy of prosthesis placement, thereby reducing the occurrence of complications such as postoperative shift 5 . However, the use of surgical navigation systems tends to increase the time of surgery, making some doctors more inclined to perform traditional surgery 167 .…”
Section: Computer‐assisted Orthopaedic Surgery Navigation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature by Rajpaul et al (2018) showed an overall improvement in restoring leg lengths compared to conventional techniques, but without strong functional benefits in the long term [15]. Despite these differences, the use of CN in THA has overall demonstrated the potential to streamline the procedure via reducing trialing, interruptions for repeat fluoroscopy, and decreased operative times compared to conventional techniques [13,16].…”
Section: Introductionmentioning
confidence: 99%